Portofolio dan Diversifikasi Investasi Pasca Covid-19 Kajian Portofolio Saham Kapitalisasi Tinggi Di Indonesia - Andreas Kiky; Michelle Suparman; Viona Marcella (LPPM Universitas BSI, 2022)
ABSTRACTIn portfolio theory, financial researchers understand that every (n) asset in portfolio could potentially reduce portfolio risk until it reaches undiversified level. Our research offers a novel idea in creation of diagonal matrix as mini simulation to proved this statement. In general, there are two main purposes of this article, first is to check whether our diagonal matrix simulation able to confirm old theory of diversification concept in financial literature. The second purpose is to check whether certain capitalization-based portfolio would be less volatile and become major answer to diversify investment asset during COVID-19 uncertainty situation. The result confirms our goal and objective with several question in the future. It is clear that diagonal matrix in this research has a limitation in the implementation. It will cause average expected return to be equal for every (n) asset portfolio. But we believe that with several input and improvement in the future, it would be very great tool to teach undergraduate students (especially financial major) to understand the diversification concept. Keywords: Portfolio Theory, Asset Diversification, COVID-19 Investment Study, Diagonal Matrix Simulation, Capitalization Based Portfolio